The Role of Angioembolization in Hepatic Trauma. Issue 11 (November 2021) - Cadili, Ali; Gates, Jonathan
The liver is one of the most commonly injured solid organs in blunt abdominal trauma. Non-operative management is considered to be the gold standard for the care of most blunt liver injuries. Angioembolization has emerged as an important adjunct that is vital to the success of the non-operative management strategy for blunt hepatic injuries. This procedure, however, is fraught with some possible serious complications. The success, as well as rate of complications of this procedure, is determined by degree and type of injury, hepatic anatomy and physiology, and embolization strategy among other factors. In this review, we discuss these important considerations to help shed further light on the contribution and impact of angioembolization with regards to complex hepatic injuries.